Antitumor carboplatin is more toxic in tumor cells when photoactivated: enhanced DNA binding - Mlcouskova, Jarmila; Stepankova, Jana; Brabec, Viktor (Journal of biological inorganic chemistry, 2012)
Carboplatin, an analogue of "classical" cis-diamminedichloridoplatinum(II) (cisplatin), is a widely used second-generation platinum anticancer drug. Cytotoxicity of cisplatin and carboplatin is mediated by platinum-DNA adducts. Markedly higher concentrations of carboplatin are required, and the rate of adduct formation is considerably slower. The reduced toxic effects in tumor cells and a more acceptable side-effect profile are attributable to the lower reactivity of carboplatin with nucleophiles, since the cyclobutanedicarboxylate ligand is a poorer leaving group than the chlorides in cisplatin. Recently, platinum complexes were shown to be particularly attractive as potential photochemotherapeutic anticancer agents. Selective photoactivation of platinum complexes by irradiation of cancer cells may avoid enhancement of toxic side-effects, but may increase toxicity selectively in cancer cells and extend the application of photoactivatable platinum complexes to resistant cells and to a wider range of cancer types. Therefore, it was of interest to examine whether carboplatin can be affected by irradiation with light to the extent that its DNA binding and cytotoxic properties are altered. We have found that carboplatin is converted to species capable of enhanced DNA binding by UVA irradiation and consequently its toxicity in cancer cells is markedly enhanced. Recent advances in laser and fiber-optic technologies make it possible to irradiate also internal organs with light of highly defined intensity and wavelength. Thus, carboplatin is a candidate for use in photoactivated cancer chemotherapy.
Keywords: kinetika; Dose-Response Relationship, Drug; DNA Damage; vztah mezi dávkou a účinkem léčiva; Carboplatin; ultrafialové záření; Drug Screening Assays, Antitumor; DNA; poškození DNA; screeningové testy protinádorových léčiv; Cell Proliferation; Tumor Cells, Cultured; skot; Antineoplastic Agents; Photochemical Processes; karboplatina; fotochemické procesy; protinádorové látky; zvířata; vztahy mezi strukturou a aktivitou; Humans; Binding Sites; Plasmids; viabilita buněk; Cattle; Cell Survival; Kinetics; proliferace buněk; Ultraviolet Rays; plazmidy; Structure-Activity Relationship; nádorové buňky kultivované; vazebná místa; lidé; Animals